First insights into the fine-scale vertical movements of a Carolina hammerhead, Sphyrna gilberti, and a hybrid between Carolina and scalloped hammerhead - Horstmyer, Lauren; Ballard, Kirsty; Daly-Engel, Toby; Stein, Kieran; Hoffmayer, Eric; Hammerschlag, Neil; Frazier, Bryan S.; Anderson, Brooke; Campbell, Beckah; Sulikowski, James (Frontiers in Marine Science, 2025)
Satellite telemetry has enabled the tracking of marine predators’ vertical and horizontal habitat use and migration patterns. These insights provide valuable information that inform management and conservation of threatened species. In this study, a scalloped hammerhead, Sphyrna lewini, (125 cm FL; immature female) a Carolina hammerhead, Sphyrna gilberti, (138 cm FL; immature female) and a scalloped/Carolina hammerhead hybrid (160 cm FL; immature male) were tagged with PSATLIFE’s off the coast of North Carolina. Tag data revealed that the Carolina hammerhead exploited a wide depth range, with a maximum depth of 846 m. Dive patterns of the scalloped hammerhead revealed differences in vertical space use, with the scalloped hammerhead primarily remaining within the top 200 m of the water column, and with a maximum depth of 380 m. The hybrid individual demonstrated similar dive patterns to those of the scalloped hammerhead, with a maximum depth of 203 m. This study presents the first vertical movement data for Carolina and hybrid scalloped/Carolina hammerheads, offering new insights into interspecific variation in depth use. Future research should explore if there are differences in habitat use and foraging strategies, as they may serve as distinguishing characteristics and support the development of effective management measures.